PENGARUH REWARD AND PUNISHMENT DAN KEPEMIMPINAN TERHADAP KINERJA PERANGKAT DESA SE KECAMATAN CERMEE BONDOWOSO DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING - Febriansyah, Febriansyah; Ediyanto, Ediyanto; Minullah, Minullah (Fakultas Ekonomi dan Bisnis, 2023)
Human Resource Management is the process of managing people through planning, recruiting, selecting, training, developing, rewarding, career, occupational health and safety, and maintaining employment until the end of working period to achieve organizational goals and improve the welfare of stakeholders. The purpose of this research was to analyze and examine the effect of reward, punishment and leadership on the performance of village officials in Cermee Bondowoso with work motivation as an intervening variable. The target population in this study was village officials in Cermee Bondowoso, as many as 40 people, who were then processed as research samples. Data analysis and hypothesis testing in this research used Partial Least Square Structural Equation Modeling (PLS-SEM). The results of direct effect hypothesis test using Smart PLS 3.0 application showed that reward and punishment have a significant positive effect on work motivation. Leadership has a significant positive effect on work motivation. Reward and punishment have a positive but not significant effect on performance. Leadership has a positive but not significant effect on performance. Work motivation has a significant positive effect on performance. Reward and punishment has a significant positive effecton performance through work motivation. Leadership has a significant positive effecton Performance through work motivation.